Macroeconomic Stability in the Climate Policy Transition - Willi Koll (Wirtschaftsdienst)
Abstract Climate policy’s goal of CO2 neutrality requires drastic structural change. This will only be accepted and successful if it takes place, in addition to social compatibility, within domestic and external economic stability. Prerequisites for this are discussed in this article.